Religiosity As A Protective Factor Against Smoking Behavior In Women: A Bibliometric Analysis Of Global Publications In 2015-2025 - Latifah Kusnul Maghfiroh; Titih Huriah (Universitas Pahlawan Tuanku Tambusai, 2026)
Smoking among women remains a significant public health concern, with growing evidence indicating that psychosocial and cultural factors, including religiosity, play an important role in shaping smoking behavior. This study aimed to map and analyze the global scientific literature on religiosity and smoking behavior among women using a bibliometric approach. A descriptive quantitative design was employed, drawing data from the Scopus database. This study included 526 English-language articles published between 2015 and 2025, selected according to inclusion criteria for publication year, subject area, document type, and relevance. A bibliometric analysis using VOSviewer was employed to examine publication trends, country contributions, citation patterns, and keyword co-occurrence networks. The results indicate a substantial increase in publications over the past decade, with a peak in 2023, and show that the United States dominates research output in this field. Highly cited studies emphasize the protective role of religiosity and spirituality in smoking cessation and health-related behaviors. Keyword analysis reveals that major research themes include religion, women, smoking, and psychological factors, with a temporal shift toward education, marital status, physical activity, and obesity in recent years. Overall, the findings suggest that religiosity is frequently conceptualized as a protective factor against smoking among women, although its influence varies across cultural and social contexts. This bibliometric mapping highlights research gaps, particularly in low- and middle-income countries. It underscores the need for culturally sensitive and gender-responsive tobacco control interventions that integrate religious and psychosocial dimensions.